Proposta metodológica de cálculo do valor da multa ambiental por meio de análise multicritério e sistemas de informação geográfica (SIG). - Oliveira, Ulisses Costa de (2023)
The current legislation related to the assessment of environmental infractions stipulates that environmental fines must be based on the type of infraction committed, considering the history of environmental infractions, the ability to pay, and the severity of the environmental infraction committed. In this context, this research aimed to develop a methodology for calculating environmental fines based on an Environmental Infraction Severity Index (EISI) using multicriteria analysis and geographic information systems to assist in the process of fining for environmental infractions. The area of application proposed encompasses the state of Ceará, Brazil, which covers an area of 148,825.6 km². For this purpose, a hybrid methodology integrating the Fuzzy Delphi (FDELPHI) and Fuzzy Analytic Hierarchy Process (FAHP) methods were used. The FDELPHI method was employed to identify the criteria and subcriteria components of the index. The FAHP method was used for calculating the relative weights of the selected criteria and sub-criteria contributing to the structure of the said index. The results indicate that Land Use and Cover is the factor that contributes most to the index, followed by criteria such as Proximity to Water Resources, Slope, Climate, Proximity to Roads, Pedology, and Geology. The EISI was divided into five severity classes (very low, low, medium, high, and very high), with the low and medium classes prevailing over the others. The weights assigned demonstrated stability and robustness when subjected to changes. Thus, through the proposed mathematical modeling, it was possible to structure the methodology for calculating environmental fines based on the spatial model of severity combined with spatial multi-criteria analysis.